Selang Kepercayaan The Generalized Confidence Interval (GCI) untuk Koefisien Variasi dari Distribusi Invers Gaussian - Aneu Nurkamilah; Abdul Kudus (Bandung Conference Series: Statistics, 2023)
Abstract. One of the distribution functions known in statistics is the Inverse Gaussian (IG) distribution. The IG distribution is used to deal with data that has a positive or right-skewed slope. The IG distribution was first introduced by Schrodinger in 1915 which originated from Brownian motion theory. In further statistical studies there is what is known as the coefficient of variation (CV), which is the ratio between the standard deviation and the mean value. In addition to point estimates, it is often desirable to find confidence intervals. One method to estimate the confidence interval of the CV coefficient is The Generalized Confidence Interval (GCI) method. In this thesis, the GCI method will be applied to the coefficient of variation of the IG distribution on PM 2.5 air pollution data. In the research process, the stages of analysis carried out include calculating the estimated parameters of the IG distribution using the maximum likelihood method, Kolmogorov-Smirnov test, calculating the values of Rλ, Rμ, dan Rθ for GCI to get the set of Rθ and calculating the 95% confidence interval for the parameter value , namely the CV parameter. Based on the calculation results, it is obtained that the PM 2.5 data in Malang City in 2023 comes from an IG-distributed population and the GCI confidence interval with a 95% confidence level for the CV of the IG distribution on PM 2.5 air pollution data in Malang City in 2023 is in the range [0.25; 0.42]. Abstrak. Salah satu fungsi distribusi yang dikenal dalam ilmu statistika adalah distribusi Invers Gaussian (IG). Distribusi IG digunakan untuk mengatasi data yang memiliki kemiringan positif atau miring ke kanan. Distribusi IG pertama kali diperkenalkan oleh Schrodinger tahun 1915 yang berasal dari teori gerak Brown. Dalam kajian statistika lebih lanjut ada yang dikenal dengan koefisien variasi (CV) yaitu perbandingan antara standar deviasi dengan nilai rata-rata. Selain nilai dugaan titik, seringkali juga diinginkan untuk mencari selang kepercayaan. Salah satu metode untuk menduga selang kepercayaan koefisien CV adalah metode The Generalized Confidence Interval (GCI). Dalam skripsi ini akan dilakukan penerapan metode GCI untuk koefisien variasi dari distribusi IG pada data pencemaran udara PM 2.5. Dalam proses penelitian tahapan analisis yang dilakukan meliputi menghitung taksiran parameter dari distribusi IG menggunakan metode maksimum likelihood, uji Kolmogorov-Smirnov, menghitung nilai Rλ, Rμ, dan Rθ bagi GCI hingga mendapatkan himpunan Rθ dan menghitung selang kepercayaan 95% untuk nilai parameter yakni parameter CV. Berdasarkan hasil perhitungan diperoleh bahwa data PM 2.5 di Kota Malang tahun 2023 berasal dari populasi yang berdistribusi IG dan selang kepercayaan GCI dengan tingkat kepercayaan 95% untuk CV dari distribusi IG pada data pencemaran udara PM 2.5 di Kota Malang tahun 2023 adalah berada di dalam rentang [0.25; 0.42].